Knowledge and Educational Intervention Pertaining To Viral Hepatitis in Adolescent Male Students of Urban and Rural Sindh, Pakistan - Anjum Shahid; Abdul Ghaffar Pirzada; Ashfaque Ahmed Memon (Journal of the Dow University of Health Sciences, 2012)
Background